2021
DOI: 10.32539/bsm.v5i6.319
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Calcipotriol 0.005% Ointment for Uremic Xerosis with Pruritus in Chronic Kidney Diseases Undergoing Hemodialysis Patients: Randomized Double Blind Clinical Trial

Abstract: Introduction: Uremic xerosis with pruritus (UXP) is a chronic cutaneous complication among patients undergoing maintenance renal dialysis. Uremic xerosis level is directly related with pruritus severity or vice versa. Uremic xerosis with pruritus may lead to discomfort and negative psychological effect. The ethiopathogenesis still unknown, Most of treatments are empirical, and there is no effective and safe therapy. Emollient has not been effective enough to improve quality of life. There is some report about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Variation in the temperature of baby oil was insignificant in its efficacy. One study reported that no positive correlation was found between the use of baby oil and improved quality of life [ 33 , 34 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the temperature of baby oil was insignificant in its efficacy. One study reported that no positive correlation was found between the use of baby oil and improved quality of life [ 33 , 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…Widyastuti et al (2022) conducted a double-masked, randomized trial to check the efficacy of Calcipotriol 0.05% ointment for uremic xerosis and CKD-ap [ 33 ]. Twice daily application of ointment showed significant improvement in xerosis and pruritis scores among ESRD patients on hemodialysis.…”
Section: Reviewmentioning
confidence: 99%